The Gollywhopper Games. The new champion - Feldman, Jody (Greenwillow Books, 2015)
Tired of living in his brother Spencer's shadow, twelve-year-old Cameron Schein considers taking an unfair advantage to win the second Golly Toy and Game Company's Gollywhopper Games, in which the brothers and other children compete by solving puzzles, answering riddles, and doing stunts.